Régulation des émotions et valeurs : le cas des collectifs bio - Denise Van Dam; Jean Nizet; Michel Streith; Lagneaux Séverine (VertigO)
This article analyzes how the leading members of four collectives in organic farming mobilize cognitive, affective and value resources to overcome negative emotions that emerge from conflicts or dysfunctions within their organization. The study has been conducted in Belgium and in France. The research invalids the leading role of cognitive reframing and shows the importance of values both in the “emotion focused” strategy and in the “situation focused” strategy. Values are present in the whole emotional episode, from the triggering event of the negative emotion to the passing of the emotion.